2023
DOI: 10.1002/chem.202300876
|View full text |Cite
|
Sign up to set email alerts
|

Polarization‐Sensitive Detector of Two‐Dimensional Multilayer Hybrid Perovskite Crystals Showing High Polarization Ratio to Weak Light

Abstract: Two-dimensional (2D) hybrid perovskite materials have been widely used for polarization-sensitive photodetection due to their fascinating optical and physical attributes. However, studies on those materials that enable strong polarized-light activities under a weak-light condition remain quite scarce. Here, by tailoring aromatic cation into 3D prototype, we have successfully obtained a new 2D hybrid perovskite, (FPEA) 2 (MA)Pb 2 Br 7 (1, where FPEA is 4-fluorophenethylammonium and MA is methylammonium). The al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…By fitting the PL decay curve of 1 with a biexponential function, the average lifetime can be calculated to be 3.587 ns (Figure b). Figure c shows a comparison of the temperature-variable electrical conductivity measured along the different directions of 1 . The results indicate that the conductivity along the in-plane direction is higher than that of the out-of-plane direction since the organic cation layer inhibits the carrier transport and enhances resistance along the out-of-plane direction.…”
Section: Resultsmentioning
confidence: 99%
“…By fitting the PL decay curve of 1 with a biexponential function, the average lifetime can be calculated to be 3.587 ns (Figure b). Figure c shows a comparison of the temperature-variable electrical conductivity measured along the different directions of 1 . The results indicate that the conductivity along the in-plane direction is higher than that of the out-of-plane direction since the organic cation layer inhibits the carrier transport and enhances resistance along the out-of-plane direction.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the photocurrent of the device remains essentially unchanged after 100 days, demonstrating its superior environmental stability. 80 Self-powered linear polarization-sensitive photodetectors can reduce energy consumption without requiring an external bias. Wang et al reported ferroelectric crystals of (isopentylammonium) 2 CsPb 2 Br 7 by a temperature-cooling method, and the device shows a stronger photoresponse.…”
Section: Applicationsmentioning
confidence: 99%
“…The estimated responsivity (detectivity) is 8.7 mA/W (4.3 × 10 11 Jones). Besides, the photocurrent of the device remains essentially unchanged after 100 days, demonstrating its superior environmental stability …”
Section: Applicationsmentioning
confidence: 99%